2002
DOI: 10.1007/s001980200030
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Ultrasound of the Heel and Some Parameters of Bone Turnover in Patients with Acromegaly

Abstract: Acromegaly caused by growth hormone (GH) hypersecretion is characterized by enhanced skeletal growth and soft tissue enlargement. Insulin-like growth factor-1 (IGF-1) is the main peripheral mediator of GH action and it has a crucial role in the maintenance of a normal bone mass. However, in some patients with acromegaly, secondary osteoporosis is observed, despite the strong anabolic effect of GH and IGF-1 in bones. It is thought to be due to hypogonadism. The bone changes are accompanied by increased turnover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…It was validated in various hormonal disorders such as menopause, primary hyperparathyroidism, acromegaly or metabolic bone diseases [2,[5][6][7]. Moreover, QUS is suitable both for monitoring of the antiresorptive therapy and for the prediction of fracture occurrences.…”
Section: Discussionmentioning
confidence: 99%
“…It was validated in various hormonal disorders such as menopause, primary hyperparathyroidism, acromegaly or metabolic bone diseases [2,[5][6][7]. Moreover, QUS is suitable both for monitoring of the antiresorptive therapy and for the prediction of fracture occurrences.…”
Section: Discussionmentioning
confidence: 99%
“…GH and its main peripheral mediator insulin-like growth factor-1 (IGF-1) stimulate proliferation, differentiation, and extracellular matrix production in osteoblastic cells. GH and IGF-1 also promote osteoclast recruitment and bone resorption activity [27][28][29][30]. In prepubertal period anabolic action of GH is responsible for longitudinal bone growth, whereas during the adolescence and early adulthood it induces skeletal maturation until the achievement of peak bone mass.…”
Section: Acromegalymentioning
confidence: 99%
“…In some studies BMD was reported to be increased or within the reference ranges, while in other papers it was decreased [17,26,[34][35][36][37]. Conflicting data on bone mineral density might be related to gonadal status, different skeletal sites being measured, various techniques employed, subject's gender, age, and activity of the disease [28,36,38]. Hypogonadal patients with acromegaly are at higher risk of osteoporosis, particularly at sites composed predominantly of trabecular bone, which has more intimate contact with the circulation and is influenced by sex steroids to a greater extent [34,39,40].…”
Section: Acromegalymentioning
confidence: 99%
See 2 more Smart Citations